Correlations between cortical gyrification and schizophrenia symptoms with and without comorbid hostility symptoms - Ferracuti, Stefano; Del Casale, Antonio; Romano, Andrea; Gualtieri, Ida; Lucignani, Martina; Napolitano, Antonio; Modesti, Martina Nicole; Buscajoni, Andrea; Zoppi, Teodolinda; Kotzalidis, Georgios D.; Manelfi, Lorenza; de Pisa, Eleonora; et al. (Frontiers in Psychiatry, 2023)
Interest in identifying the clinical implications of the neuropathophysiological background of schizophrenia is rising, including changes in cortical gyrification that may be due to neurodevelopmental abnormalities. Inpatients with schizophrenia can show abnormal gyrification of cortical regions correlated with the symptom severity. Our study included 36 patients that suffered an acute episode of schizophrenia and have undergone structural magnetic resonance imaging (MRI) to calculate the local gyrification index (LGI). In the whole sample, the severity of symptoms significantly correlated with higher LGI in different cortical areas, including bilateral frontal, cingulate, parietal, temporal cortices, and right occipital cortex. Among these areas, patients with low hostility symptoms without a history of involuntary treatment (LHS) compared to patients with high hostility symptoms and a history of compulsory treatment (HHS) showed significantly lower LGI related to the severity of symptoms in bilateral frontal and temporal lobes. Severity of psychopathology correlated with higher LGI in large portions of the cerebral cortex, possibly expressing abnormal neural development in schizophrenia. These findings could pave the way for further studies and future tailored diagnostic and therapeutic strategies.